Exploring the Perceptions of Moroccan EFL learners Towards Teachers’ Use of Humor in the Classroom: the Case of Students of English in Sidi Mohammed Ben Abdellah University, Fez - Azz Eddine Diouani (Universitas Islam Malang, 2020)
For the purpose of enhancing teachers’ effectiveness and students’ learning, unnumbered teaching strategies have been researched and implemented in the area of English language teaching and learning, one of which is the incorporation of appropriate types of teacher’ humor in the classroom. Therefore, the primary aim of this study was to explore Moroccan EFL learners' perceptions’ of teachers’ use of humor in the EFL classroom. To this end, 110 Moroccan EFL learners participated in this study. As such, quantitative and qualitative data were collected via means of questionnaires and semi-structured interviews. The findings gathered seem to suggest that the incorporation of humor in the classroom is highly appreciated by the participants mainly because such incorporation has the potential to help create a relaxed classroom atmosphere, foster a good student-teacher relationship and thus, contribute, more or less, to promoting students’ learning and teachers’ effectiveness.